Ilocution Speaking Action in Advertising Persuasion Discourse on Spotify/TINDAK TUTUR ILOKUSI DALAM WACANA PERSUASI IKLAN DI SPOTIFY - Fina Nabilah Layaliya; Bernadus Wahyudi Joko Santoso (STAI Ma'had Aly Al-Hikam Malang, 2022)
One example of the use of language is in advertising. In advertising, the use of language is an important aspect for the success of advertising. Sentences in advertising language can be included in the study of speech acts. Speech acts are related to discourse because in their complete form, discourse can be in the form of text, both written and spoken. Therefore, in examining Spotify's advertising discourse, speech act analysis can be used as a knife of study. This study uses a qualitative approach and is a qualitative descriptive study. In collecting data, the method used in this research is the method of listening. The basic technique used is the tapping technique and the next technique is the note-taking technique. While at the data analysis stage using the equivalent method. In the matching method, the technique used is the Determining Element Sorting (PUP) technique.